384/3. because it comes out even..128..the rest won't
Answer:
9
Step-by-step explanation:
(-9)^1/3 * (-81)^1/3
We can rewrite -81 as 9 * -9
So it can be rewritten as:
(-9)^1/3 * (9*-9)^1/3
Since they are all raised to the 1/3, we can combine the bases:
(-9*9*-9)^1/3 =
(9*9*9)^1/3, because the two negatives turn into a positive:
So this is basically:
(9^3)^1/3 = 9^1 = 9
Answer:
120
Step-by-step explanation:
66 + (2* 10*5)- 46
66+20×5−46
66+100−46
166−46
= 120
Brainlist Pls!
Selections B and D both appear to be appropriate.
B) (x+8)² + (y+5)² = 13
D) (x+8)² + (y+5)² = 13
_____
The center is at the midpoint of the diameter, ((-10-6)/2, (-8-2)/2) = (-8, -5). For center (h, k) and radius r, the equation is
(x -h)² +(y -k)² = r²
(x -(-8))² +(y -(-5))² = (√13)²
(x+8)² + (y+5)² = 13
Answer:
mews jh
Step-by-step explanation: